2014
DOI: 10.1186/1471-2393-14-99
|View full text |Cite
|
Sign up to set email alerts
|

Is essential newborn care provided by institutions and after home births? Analysis of prospective data from community trials in rural South Asia

Abstract: BackgroundProvision of essential newborn care (ENC) can save many newborn lives in poor resource settings but coverage is far from universal and varies by country and place of delivery. Understanding gaps in current coverage and where coverage is good, in different contexts and places of delivery, could make a valuable contribution to the future design of interventions to reduce neonatal mortality. We sought to describe the coverage of essential newborn care practices for births in institutions, at home with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 58 publications
(78 reference statements)
6
43
0
Order By: Relevance
“…Specific components of delivery care which are rapidly increasing in many middle‐income countries, such as increased use of analgesia, labour induction and augmentation, and caesarean delivery, may negatively impact on breastfeeding and contribute to a narrowing of the advantage conferred by facility care. An investigation of delivery setting and essential newborn care using data from prospective trials in South Asia reported that the proportion of women experiencing skin‐to‐skin contact with their infant within 30 min of birth was lower in institutional delivery settings compared to home (Pagel et al, ). Among facility births, we consistently observed a higher prevalence of optimal early breastfeeding practices in public sector births compared to births in private facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Specific components of delivery care which are rapidly increasing in many middle‐income countries, such as increased use of analgesia, labour induction and augmentation, and caesarean delivery, may negatively impact on breastfeeding and contribute to a narrowing of the advantage conferred by facility care. An investigation of delivery setting and essential newborn care using data from prospective trials in South Asia reported that the proportion of women experiencing skin‐to‐skin contact with their infant within 30 min of birth was lower in institutional delivery settings compared to home (Pagel et al, ). Among facility births, we consistently observed a higher prevalence of optimal early breastfeeding practices in public sector births compared to births in private facilities.…”
Section: Discussionmentioning
confidence: 99%
“…An educated woman is more likely to understand the consequences of traditional medicines or services from TBA, usually in rural areas that lead to unattended home deliveries [18,71]. To rise above the long-established mindset of the community and rebel against the conventional flow to seek modern medical help, higher education would be necessary to avert maternal deaths [72].…”
Section: Plos Onementioning
confidence: 99%
“…Detailed questionnaires were used to collect information regarding the intrapartum care of all enrolled women. In this study, we use information regarding newborn care practices gathered in the control clusters of the trials to examine how these practices changed over time in the absence of the trial interventions; we were not evaluating the trial interventions, so did not use data from the women’s group intervention clusters [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…There have also been efforts to improve aspects of newborn care for women giving birth at home without an SBA, for example through the promotion of clean delivery kits [ 7 , 8 ]. However the coverage of protective birth practices remains incomplete and variable across settings [ 9 15 ]. Observed improvement in the coverage of essential newborn care could be due to more women having a skilled attendant at delivery, improvements in the quality of skilled attendance, improvement in practices at unattended deliveries at home or a combination of all three.…”
mentioning
confidence: 99%
See 1 more Smart Citation